Calpain‐1 is associated with adverse relapse free survival in breast cancer: a confirmatory study. Issue 7 (11th January 2016) - Pu, Xuan; Storr, Sarah J; Ahmad, Narmeen S; Chan, Stephen Y; Moseley, Paul M; Televantou, Despina; Cresti, Nicola; Boddy, Alan; Ellis, Ian O; Martin, Stewart G
Abstract : Aims: Calpain‐1 is a ubiquitously expressed calcium‐activated intracellular cysteine protease. Altered expression of calpain system proteins has been implicated in cancer progression and response to chemotherapy. Methods and results: The aim of the current study was to confirm previous data that suggested that calpain‐1 expression is associated with relapse‐free survival in trastuzumab‐treated breast cancer patients ( n = 93). An expanded patient cohort from Nottingham ( n = 194; including 72 of the previous cohort) and an independent patient cohort from Newcastle ( n = 87) were used. All patients received trastuzumab following adjuvant therapy according to local guidelines with expression of calpain‐1 investigated using standard immunohistochemistry. Results show that calpain‐1 expression is associated with relapse‐free survival in both the Nottingham ( P = 0.01) and Newcastle ( P = 0.019) cohorts, with high expression associated with adverse relapse‐free survival. Expression was also associated with poor relapse‐free survival when patient cohorts were combined ( n = 281, P = 0.01). Calpain‐1 remained, from multivariate analysis, an independent marker for relapse‐free survival in the Newcastle cohort [hazard ratio (HR) = 5.169; 95% confidence interval (CI) 1.468–18.200; P = 0.011]. Conclusions: Calpain‐1 expression is associated with poor relapse‐free survival in breast cancer patients treated with trastuzumab. Further work is warranted to standardize and develop methodology with a view to potentially introducing assessment of this important biomarker into clinical practice.